Chuanzhitongluo capsule ameliorates microcirculatory dysfunction in rats: Efficacy evaluation and metabolic profiles - Sun, Yuanfang; Cheng, Guoliang; Du, Lijing; Gan, Yu; Li, Bing; Yan, Shikai; Shao, Mingguo; Jin, Huizi; Li, Shasha (Frontiers in Pharmacology, 2022)
Background: Ischemic stroke is a leading cause of mortality and disability worldwide. Microcirculatory dysfunction is the foremost hindrance for a good clinical prognosis in ischemic stroke patients. Clinical researches show that Chuanzhitongluo capsule (CZTL) has a curative effect during the recovery period of ischemic stroke, which contributes to a good prognosis. However, it is not known whether CZTL treats ischemic stroke by ameliorating microcirculation dysfunction. Objective: In this study, we investigated the influence of CZTL on microcirculation and its underlying mechanism. Methods: A rat model of acute microcirculatory dysfunction was established by stimuli of adrenaline and ice water. The microcirculatory damage in model rats and the efficacy of CZTL were assessed by detecting laser speckle contrast imaging, coagulation function, hemorheology, vasomotor factor and microcirculation function. The potential mechanism of CZTL action was explored by the untargeted metabolomic analysis based on ultra-performance liquid chromatography-quadrupole-time of flight-mass spectrometry. Results: Laser speckle contrast imaging showed that model rats suffered low perfusion in ears, feet and tails, and CZTL treatment increased microcirculatory blood flow. Coagulation function detection results showed that CZTL diminished the reduction of thrombin time, prothrombin time, activated partial thromboplastin time and the elevated fibrinogen level caused by acute microcirculatory dysfunction. Furthermore, CZTL could recover the increased blood viscosity as well as the abnormal vasomotor and microcirculation function in rats with acute microcirculatory dysfunction. Metabolomics analysis indicated that CZTL might regulate sphingolipid metabolism and arachidonic acid metabolism to exert protective effects on microcirculation. Conclusion: These results elucidated that CZTL was highly effective against microcirculatory dysfunction and its potential mechanisms related with the modulation of sphingolipid and arachidonic acid metabolic pathways. The present study provided a new perspective on the clinical application of CZTL, and it contribute to explore novel therapeutic drug against microcirculatory dysfunction.